Powtoon Video with Reading Aloud for Better Pronunciation in Primary Students: Video Powtoon dengan Pembacaan Lisan untuk Meningkatkan Pelafalan pada Siswa Sekolah Dasar - Ajeng, Hera Galuh; Megawati, Fika (Universitas Muhammadiyah Sidoarjo, 2025)
Abstract : General background: Pronunciation is a fundamental component in English language learning, especially for primary school students, as it affects communication clarity and confidence. Specific background: In many Indonesian primary schools, pronunciation teaching is often limited to conventional methods without engaging multimedia tools, leading to low motivation and varied achievement. Knowledge gap: Limited research has applied reading aloud activities with Powtoon video to support pronunciation improvement in primary-level learners. Aims: This study investigates the use of Powtoon video integrated with reading aloud to improve the pronunciation of 24 sixth-grade students at a primary school in Pasuruan. Results: Using a quantitative pre-experimental design with pre-test and post-test, findings show a significant increase in post-test scores (M=79.27) compared to pre-test scores (M=59.79), with a paired t-test value of -24.472, p < 0.05, indicating a statistically significant difference. Novelty: This research applies Powtoon not for reading comprehension but specifically for pronunciation through reading aloud, targeting young learners. Implications: The results suggest that integrating Powtoon into pronunciation lessons can increase student engagement, provide multisensory learning experiences, and improve pronunciation consistency. Highlights : Integrates Powtoon video with reading aloud for pronunciation learning Significant improvement in post-test pronunciation scores Offers an engaging multimedia-based approach for young learners Keywords : Powtoon, Primary School, Pronunciation, Reading Aloud, Multimedia Learning